The Opportunity to Develop Buffalo Production Based on Food Crop Residues - Kuswandi . (Indonesian Center for Animal Research and Development, 2007)
Buffalo’s meat is an alternative commodity to meet the national meat requirement despite its low contribution (1.93%) compared to cattle’s meat (22%). Compared to other livestock, buffalo has some benefit characteristics, such as higher ability to utilize fibrous feed, higher metabolism capacity, etc. Agriculture crop residues are feed resources which are abundant and very potential to be used the whole year. Buffalloes can utilize the fibrous residues as roughages and agro industrial by products to meet their nutrient requirement for protein, energy and minerals. Arrangement of feed supply based on harvest season is expected to solve the problem of feed deficiency. Food crop-buffalo integration is beneficial to maintain soil fertility and utilization of crop residues as feed. Key words: Buffalo, crop residues, integration